Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1590/1980-5373-mr-2016-1007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aging at 450°C on the Pitting Corrosion Resistance and Toughness of AISI 317L Steel Welded by GTAW and FSW

Abstract: Austenitic stainless steels are high corrosion resistant alloys widely used in many industrial fields. Among this family of steels, AISI 317L stands out due to its higher localized corrosion resistance when compared to the traditional grades AISI 304L and AISI 316L. In some applications in oil refineries, the AISI 317L is being specified for services at moderately high temperatures. At the same time as it is sought to use new stainless steels, is also desirable to apply and develop emerging welding processes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
(11 reference statements)
1
2
0
1
Order By: Relevance
“…The formation of the ferrite phase with columnar morphology due to the solidification pattern and three primary austenite morphologies were observed in both conditions, which are grain boundary allotriomorphic, Widmanstätten and intragranular. These morphologies are typically found in duplex and super duplex stainless steels, agreeing with the literature 25,26 , and differ significantly from those observed for the austenitic stainless steel metal welds, including 317L 9,19,27 , because ferrite becomes more stable over a wide temperature range and the solid-state phase transformation from ferrite to austenite stars at a lower temperature.…”
Section: Welded Joints Before Ahtsupporting
confidence: 87%
See 2 more Smart Citations
“…The formation of the ferrite phase with columnar morphology due to the solidification pattern and three primary austenite morphologies were observed in both conditions, which are grain boundary allotriomorphic, Widmanstätten and intragranular. These morphologies are typically found in duplex and super duplex stainless steels, agreeing with the literature 25,26 , and differ significantly from those observed for the austenitic stainless steel metal welds, including 317L 9,19,27 , because ferrite becomes more stable over a wide temperature range and the solid-state phase transformation from ferrite to austenite stars at a lower temperature.…”
Section: Welded Joints Before Ahtsupporting
confidence: 87%
“…Several works [8][9][10] , which studied dissimilar welding among austenitic stainless steels and other types of stainless steels, have reported that higher delta-ferrite formation in the weld metal associated with higher Mo concentration contributes to the precipitation of these deleterious secondary phases, leading to a decrease of the pitting and stress corrosion cracking resistance of the welded joint. Additionally, as the δ-ferrite is more easily electrochemical attacked than austenite, the corrosion process may be accelerated depending on the environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Para tal, uma investigação da composição química do metal de adição com relação a quantidade de ferrite δ e a partição dos elementos no metal na ZF e ZTA deve ser feita para manter as propriedades de corrosão e mecânica das juntas soldadas mais similar possível à do metal base. Recentemente, os aços inoxidáveis duplex têm sido investigados como metal de adição para soldagem de aços inoxidáveis austeníticos ricos em Mo numa tentativa de mitigar problemas mecânicos, metalurgicos e de corrosão que surgem devido à precipitação de fases deletérias tais como as fases sigma e Chi, durante a soldagem destes aços [6][7][8]. No entanto, não foram encontrados na literature, estudos relacionados especificamente a esta aplicação para os aços 317L.…”
Section: Introductionunclassified